Augmented IFN-γ and TNF-α Induced by Probiotic Bacteria in NK Cells Mediate Differentiation of Stem-Like Tumors Leading to Inhibition of Tumor Growth and Reduction in Inflammatory Cytokine Release; Regulation by IL-10 - Bui, Vickie T.; Tseng, Han-Ching; Kozlowska, Anna; Maung, Phyu Ou; Kaur, Kawaljit; Topchyan, Paytsar; Jewett, Anahid (Frontiers in Immunology, 2015)
Our previous reports demonstrated that the magnitude of natural killer (NK) cell-mediated cytotoxicity correlate directly with the stage and level of differentiation of tumor cells. In addition, we have shown previously that activated NK cells inhibit growth of cancer cells through induction of differentiation, resulting in the resistance of tumor cells to NK cell-mediated cytotoxicity through secreted cytokines, as well as direct NK-tumor cell contact. In this report, we show that in comparison to IL-2 + anti-CD16mAb-treated NK cells, activation of NK cells by probiotic bacteria (sAJ2) in combination with IL-2 and anti-CD16mAb substantially decreases tumor growth and induces maturation, differentiation, and resistance of oral squamous cancer stem cells, MIA PaCa-2 stem-like/poorly differentiated pancreatic tumors, and healthy stem cells of apical papillae through increased secretion of IFN-γ and TNF-α, as well as direct NK-tumor cell contact. Tumor resistance to NK cell-mediated killing induced by IL-2 + anti-CD16mAb + sAJ2-treated NK cells is induced by combination of IFN-γ and TNF-α since antibodies to both, and not each cytokine alone, were able to restore tumor sensitivity to NK cells. Increased surface expression of CD54, B7H1, and MHC-I on NK-differentiated tumors was mediated by IFN-γ since the addition of anti-IFN-γ abolished their increase and restored the ability of NK cells to trigger cytokine and chemokine release; whereas differentiated tumors inhibited cytokine release by the NK cells. Monocytes synergize with NK cells in the presence of probiotic bacteria to induce regulated differentiation of stem cells through secretion of IL-10 resulting in resistance to NK cell-mediated cytotoxicity and inhibition of cytokine release. Therefore, probiotic bacteria condition activated NK cells to provide augmented differentiation of cancer stem cells resulting in inhibition of tumor growth, and decreased inflammatory cytokine release.